MetaEmotions at School: A Program for Promoting Emotional and MetaEmotional Intelligence at School; a Research-Intervention Study - Antonella D'Amico; Alessandro Geraci (MDPI AG, 2022)
MetaEmotions at Schools is a SEL program that aims at promoting the culture of emotional and metaemotional intelligence in schools, and at improving emotional awareness both among teachers and students. It is a train-the-trainers program that unfolds in five steps, respectively, aimed at stimulating teachers and students to: (1) develop emotional literacy; (2) create emotionally inclusive environments; (3) build tools, materials and methods for emotionally inclusive classes; (4) develop didactic method mediated by emotions; (5) become ambassadors of the metaemotional intelligence at school and beyond. In this study, we report some results of the first application of the training program, focusing in particular on the effect of the program on emotional and metaemotional intelligence of participants. A total of 264 pupils from lower secondary schools of five Italian cities were recruited and divided in 9 intervention and 9 comparison classes. All participants were administered with emotional and metaemotional intelligence assessment tools before and after the training program. The results showed that emotional abilities scores in the intervention groups tended to be stable over time compared to the comparison groups ones which tended to decrease. Moreover, the pupils showed a reduced tendency to overestimate their emotional abilities. These results pave the way to further applications of the program and shed the light on areas of improvement.